Comparison of ultra-low dose chest CT scanning protocols for the detection of pulmonary nodules: a phantom study. Issue 5 (October 2019) - Milanese, Gianluca; Silva, Mario; Frauenfelder, Thomas; Eberhard, Matthias; Sabia, Federica; Martini, Chiara; Marchianò, Alfonso; Prokop, Mathias; Sverzellati, Nicola; Pastorino, Ugo
Purpose: To test ultra-low-dose computed tomography (ULDCT) scanning protocols for the detection of pulmonary nodules (PN). Methods: A chest phantom containing 19 solid and 11 subsolid PNs was scanned on a third-generation dual-source computed tomography (CT) scanner. Five ULDCT scans (Sn100kVp and 120, 70, 50, 30, and 20 reference mAs, using tube current modulation), reconstructed with iterative reconstruction (IR) algorithm at strength levels 2, 3, 4, and 5, were compared with standard CT (120kVp, 150 reference mAs, using tube current modulation). PNs were subjectively assessed according to a 4-point scale: 0, nondetectable nodule; 1, detectable nodule, very unlikely to be correctly measured; 2, detectable nodule, likely to be correctly measured; 3, PN quality equal to standard of reference. PN scores were analysed according to the Lung Imaging Reporting and Data System (Lung-RADS), simulating detection of nodules at baseline and incidence screening round. Results: For the baseline round, there were 17 Lung-RADS 2, 4 Lung-RADS 3, 8 Lung-RADS 4A, and 1 Lung-RADS 4B PNs. They were detectable in any ULDCT protocol, with the exception of 1 nondetectable part-solid nodule in 1 scanning protocol (120 reference mAs; IR strength: 3). For the incidence round, there were 4 Lung-RADS 2, 14 Lung-RADS 3, 2 Lung-RADS 4A, and 10 Lung-RADS 4B PNs. Ten were nondetectable in at least one ULDCT dataset; however, they were at least detectable in ULDCT with 70 reference mAs (IR strength: 4 and 5). Conclusions: ULDCT scanning protocols allowing the detection of PNs can be proposed for the purpose of lung cancer screening.